Estimating supply response of milk production to price and non-price factors in South Africa - Manaka, Mateadi Thabiso (My University, 2019)
The South African dairy industry is approximately 0.5% of the global production. The production of milk contributes to exports, manufacturing, employment, food security and development of other producers of agricultural products such as maize and soya bean. Following the deregulation of the agricultural markets in 1996, the dairy industry has seen a decline in the number of producers, with Milk Producer Organisation noting that between 2008 and 2015 there has been a decline of 58%. Therefore, the decline in producers necessitates the need to understand the nature and factors that influence the remaining producers to continue producing. This study, therefore, was undertaken to examine the supply response of milk production to price and non-price factors in South Africa using the Nerlovian Partial adjustment model. In that regard, the historical data for the period of 1996 to 2014 was used and analysed in Eviews 10 software. The short-run and Long-run elasticities of milk production were found to be inelastic. The results of the study further indicated that milk production was responsive to changes in price of beef, technology, previous production, and temperature. Given the study findings, thus recommendations made are that technological research and advancement, such as animal cross breeding is necessary to improve production of milk in the country. Furthermore, better price incentives such as price floors and subsidies are necessary in the industry, to encourage more milk production and reduce likelihood of farmers to switch from milk to beef, given the changes in price.
Thesis (M. Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2019
Keywords: Milk production; Price; Non-price factors; Supply response; Nerlovian adjustment model; Milk production -- South Africa; Milk supply -- South Africa